PRIMER REGISTRO DEL TIGRILLO (LEOPARDUS WIEDII, SCHINZ 1821) Y DEL GATO MONTÉS (LYNX RUFUS, KERR 1792) EN LA RESERVA DE LA BIÓSFERA DE TEHUACÁN-CUICATLÁN, OAXACA, MÉXICO - Botello, Francisco; Illoldi-Rangel, Patricia; Linaje, Miguel; Sánchez-Cordero, Víctor (Instituto de Ecología, A.C., 2006)
Using camera-traps, two new records of margay (Leopardus wiedii) and two of lynx (Lynx rufus) were obtained at the Biosphere Reserve de Tehuacán-Cuicatlán, Oaxaca, Mexico, in 2003 and 2004. These are the first records documenting the presence of both species in this reserve.